Knowledge of and Attitudes Toward Clinical Depression Among Health Providers in Gujarat, India - Santiago Almanzar; Nirsarg Shah; Suril Vithalani; Sandip Shah; James Squires; Raghu Appasani; Craig L. Katz (Ubiquity Press, 2014)
Background: Clinical depression is a major leading cause of morbidity and mortality but it is oftentimes overlooked and undertreated. The negative perception and lack of understanding of this condition prevents millions of people from seeking appropriate and on-time medical help, leading to distress and increased burden for affected people and their families. The implementation of public education campaigns and training of non-psychiatric health professionals on mental health and clinical depression has been neglected in several countries, including India, which is the second most populous country in the world with a population of more than 1.2 billion people, almost one-fifth of the world's population. Objective: This study sought to explore the knowledge and attitudes toward the diagnosis and treatment of clinical depression in nonpsychiatric health care providers in Vadodara, Gujarat, India. Methods: A cross-sectional survey was conducted over a 4-week period In Gujarat, India among resident physicians and community health workers about their knowledge and views on clinical depression. Findings: We found considerable stigma and misinformation about depression especially among health care workers in India. Most of the community health workers had a great deal of difficulty when defining clinical depression, and a large majority said that they never heard about depression or its definition and although the overwhelming majority of respondents did not believe that clinical depression results from a punishment from God (82% disagreed or strongly disagreed with this belief) or evil spirits (77.5%), a much smaller proportion disagreed with the assertions that depression was either solely due to difficult circumstances (38.2%) or that sufferers only had themselves to blame (47.2%). Meanwhile, only 32.6% disagreed with the position that clinical depression is a sign of weakness and 39.4% disagreed with the statement that suicide was a sign of weakness. Conclusions: Our findings underscore the considerable public health priority facing India's policymakers and planners to better educate more non-psychiatric physicians and community health workers to identify, understand, and respond to early signs of mental illnesses, especially clinical depression.